CFIA-Turbidimetric and Photometric Determination of Vitamin B9 (Folic acid) Using LEDs as a Source of Irradiation and Two Solar Cells as an Energy Transducer (Baghdad Science Journal, 2025)
A specific, sensitive and simple method was used for the determination of: vitamin B9 (Folic acid) in pure and pharmaceutical formulations using continuous flow injection analysis. The method is based on formation of ion pair compound between folic acid and ammonium molybdate in an aqueous medium to obtain a gray precipitate complex, using homemade; Ayah-6SX1-ST-2D solar cell CFI Analyzer. Optimum parameters was studied to increase the sensitivity for developed method. The linear range for the calibration graph was 0.01-0.6 mMol.L-1 of vitamin B9 and LOD was 131.994 ng/sample with correlation coefficient ( r ) of 0.9810, RSD% was lower than 0.1%, (n=9) for the determination of vitamin B9 at concentration (0.07and 0.5) mMol.L-1 respectively. The developed method was applied successfully for the determination of vitamin B9 in pharmaceutical tablets. A comparison was made between two methods: developed method and the classical UV spectrophotometric method at ?max=255 nm, by using the standard addition method via the use of paired t-test. It showed that there was no significant difference between the developed method and the classical method for determination vitamin B9 at 95% confidence level.